1990
DOI: 10.1111/j.1365-2826.1990.tb00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Rat Oxytocin Gene by Estradiol

Abstract: Oxytocin (OT) plays a role in reproduction at the level of the pituitary and mammary glands and uterus. This OT is synthesized in the hypothalamo-neurohypophyseal system (HNS). A number of observations have suggested that estrogens regulate the production of OT in the HNS. In this study the effect of 17beta-estradiol on the activity of the OT gene promoter was examined as well as the effect of 17beta-estradiol in vivo on OT messenger ribonucleic acid (mRNA) and peptide revels in the rat HNS. Vasopressin (VP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(12 citation statements)
references
References 44 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…However, the literature on E 2 regulation of Avp and Oxt in the SON is mixed. Some studies showed that E 2 upregulated (Roy et al, 1999), downregulated (Shughrue et al, 2002; Van Tol et al, 1988), or had no effect on expression (Peter et al, 1990; Rhodes et al, 1981). Our data add to this literature on the SON by showing that long-term E 2 treatment upregulates expression of genes involved in nonapeptide signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature on E 2 regulation of Avp and Oxt in the SON is mixed. Some studies showed that E 2 upregulated (Roy et al, 1999), downregulated (Shughrue et al, 2002; Van Tol et al, 1988), or had no effect on expression (Peter et al, 1990; Rhodes et al, 1981). Our data add to this literature on the SON by showing that long-term E 2 treatment upregulates expression of genes involved in nonapeptide signaling.…”
Section: Discussionmentioning
confidence: 99%
“…6. Initially, it was believed that OXT expression was directly regulated by the binding of estrogen to ERE in the promoter region (42,46). However, this mechanism is now in doubt as the ERE in the promoter of OXT is not a good match to the ERE consensus sequence (51,29).…”
Section: Discussionmentioning
confidence: 99%
“…Infusing oxytocin antagonist into the postpartum rat’s NAcc, which is necessary for the consolidation of maternal memory as described in Section 4, impairs the reemergence of maternal behavior when tested 10 days after a 1 hour maternal experience (D’Cunha et al, 2011). While oxytocin expression can also be regulated by estrogen (Richard and Zingg, 1990), this may not occur strongly in the oxytocin-releasing neurons of the rat paraventricular nucleus (Peter et al, 1990; Gimpl and Fahrenholz, 2001), so that a more complete model of maternal sensory memories may require incorporation of distinct roles for both these hormones. Indeed, it should be emphasized that estrogens are only one of the important components of the molecular cascades that regulate maternal memory, but a complete review of all the potential players would be beyond the scope of the current review.…”
Section: A Potential Role For Estrogen In Facilitating Maternal Mementioning
confidence: 99%